Corporate restructuring and creditor power: Evidence from European insolvency law reforms - Closset, Frédéric; Großmann, Christoph; Kaserer, Christoph; Urban, Daniel (Journal of Banking & Finance, 2023)
In an attempt to match US bankruptcy law, many European countries have reformed their insolvency laws towards a regime that fosters corporate restructuring. This paper evaluates the implications of these reforms. Based on a staggered difference-in-differences analysis around eight insolvency reforms in 15 European countries, this paper finds a relative increase in the cost of debt by about 50 bps in countries with such a reform. The effect is more pronounced among firms being closer to default. As a result of increased cost of debt financing, firms cut investment, innovation, and employee pay. In addition, firms are also more likely to turn into zombies post-treatment. Overall, the results are consistent with the view that creditors may be negatively affected by insolvency law reforms oriented towards restructuring and, thus, demand higher risk premia. This, in turn, causes real effects in the corporate sector.